2019
DOI: 10.1175/jas-d-18-0216.1
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Lifting Condensation Level on Low-Level Outflow and Rotation in Simulated Supercell Thunderstorms

Abstract: This paper reports on results of idealized numerical simulations testing the influence of low-level humidity, and thus lifting condensation level (LCL), on the morphology and evolution of low-level rotation in supercell thunderstorms. Previous studies have shown that the LCL can influence outflow buoyancy, which can in turn affect generation and stretching of near-surface vertical vorticity. A less explored hypothesis is tested: that the LCL affects the relative positioning of near-surface circulation and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(7 citation statements)
references
References 60 publications
0
7
0
Order By: Relevance
“…We have refrained from a detailed analysis of updrafts in the PBL because the structure of such updrafts is likely to be strongly dependent on a range of processes, such as dry convection in the PBL, cold pools, synoptic scale forcing for ascent, dynamics within the lower parts of existing updrafts, and terrain features to name a few. It is possible that such a framework for extending updraft properties into the PBL could be developed in the future through an analysis of dynamic and buoyant pressure accelerations below cloud base (e.g., Brown & Nowotarski, 2018) and along the edge of cold pools (e.g., Bryan & Rotunno, 2014; Jeevanjee & Romps, 2015); however, we leave such analysis to future work.…”
Section: Map Formulationmentioning
confidence: 99%
“…We have refrained from a detailed analysis of updrafts in the PBL because the structure of such updrafts is likely to be strongly dependent on a range of processes, such as dry convection in the PBL, cold pools, synoptic scale forcing for ascent, dynamics within the lower parts of existing updrafts, and terrain features to name a few. It is possible that such a framework for extending updraft properties into the PBL could be developed in the future through an analysis of dynamic and buoyant pressure accelerations below cloud base (e.g., Brown & Nowotarski, 2018) and along the edge of cold pools (e.g., Bryan & Rotunno, 2014; Jeevanjee & Romps, 2015); however, we leave such analysis to future work.…”
Section: Map Formulationmentioning
confidence: 99%
“…5, but for the DJF period. Blanchard 1998;Thompson et al 2003) that has been shown to impact the positioning and strengthening of nearsurface circulation in supercell environments (Brown and Nowotarski 2019). This positive trend in CAPE places SC day values beyond the bounds of HSLC CAPE criteria.…”
Section: E Environmental Characteristics 1) Mammentioning
confidence: 95%
“…Static stability measures the gravitational resistance of the atmosphere to vertical displacements (Bluestein, 1992). The burst of KHI, which is the major triggering source for turbulence (Sharman et al, 2012), is characterized by the occurrence of Ri falling below a critical value that is frequently taken as 1/4 (Fritts & Alexander, 2003).…”
Section: Prestorm Environment From Proximity Soundingsmentioning
confidence: 99%
“…The probability distributions of convective available potential energy (CAPE) and 0–6 km bulk shear vary greatly by severe weather (Púčik et al., 2015). For instance, low‐level (0–1 km) vertical wind shear and lifting condensation levels (LCLs) can skillfully distinguish between nontornadic and tornadic supercells (Brown & Nowotarski, 2019). Therefore, attempts have been made to infer the environment of convective storms based on a variety of proximity sounding parameters.…”
Section: Introductionmentioning
confidence: 99%